Macro Approach in Economic Crime Response Technology in the Age of Global Transformation - Alan Setiawan, Dian; ., Abdul Rohman; Fadhly Jambak, Fabian; Umbara, Alfiyan; Wildan S, Fitrah (KnE Social Sciences, 2023)
The economic interest that dominates the pattern of modern human life causes the most prominent global transformation in terms of economic activity. Related to this, a macro approach is needed in overcoming technology-based economic crimes. The urgency of this research is expected to provide input for the development of legal science, specifically in Judicial Law and Economic Criminal Law related to cybercrime and make improvements in the provisions of laws and regulations relating to telematics crimes, especially in terms of electronic transactions. This study uses normative legal research. This study uses secondary data and primary data as supporting data. The results of this study show that overcoming technological economic crimes requires a multi-aspect concept because the nature of technological economic crimes is very complex. Its complexity continues to grow following the flow of global transformation in the economy. Therefore, the concept of handling it must be done with a multi-aspect concept. Keywords: economic, crimes, technology, global